Study Intertekstual Yesaya 42: 1-4 dan Matius 12:18-21 - Tarigan, Wahyu Triwira (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Intertextual is an approach to understand a text as an insert from other texts. A text is understood not to stand alone. A text is composed of quotations or other text sources. One text that requires intertextual study is the text of Matthew 12:18-21 which quotes Isaiah 42:1-4, which is the longest quotation of the Old Testament in the Gospels. Three main points of study were carried out on the intertextuality of the two texts: First, what is the context and meaning of the text of Isaiah 42:1-4? Second, what is the context and meaning of the text of Matthew 12:18-21? Third, How does Matthew quote Isaiah?Keywords: Intertextuality; Isaiah 42; Matthew 12.